Desempenho escolar: análise comparativa em função do sexo e percepção dos estudantes - Osti, Andréia [UNESP]; Martinelli, Selma De Cássia (Universidade de São Paulo (USP), Faculdade de Educação, 2014)
This paper discusses the results of an investigation of academic achievement by gender and student perception of the expectations of their teachers. 120 students from the 5th year of primary education municipal public schools in the metropolitan region of Campinas city participated in the research: 60 of the students have satisfactory academic performance and the other 60 have unsatisfactory performance. We used a scale of student perception of teacher expectations and, to measure academic performance, we considered the grade teachers assigned to students. Research results revealed significant differences between boys and girls in the group of students with unsatisfactory performance, because most of them (83.3%) were male. On the other hand, there were no statistically significant differences between boys and girls in the group with satisfactory academic performance, although girls' average academic performance was higher. Regarding the perception of their teachers, we observed differences in both groups. Students with satisfactory performance have the perception that they are more praised and more often chosen to assist the teacher in the classroom while underperforming students believe they receive more criticism from their teachers and are seen as more unruly. The data allow discussing student-teacher bond, the influence of experience at the time of learning and how it influences the interest and motivation of students.

O presente artigo investigou o desempenho escolar em função do sexo e a percepção de alunos em relação às expectativas de seu professor. Participaram da pesquisa 120 alunos do 5º ano do ensino fundamental de escolas públicas municipais da região metropolitana de Campinas, dos quais 60 alunos têm desempenho escolar satisfatório e 60 têm desempenho insatisfatório. Foi utilizada uma escala de percepção de alunos acerca das expectativas dos professores; já para medir o desempenho escolar foi considerado o conceito atribuído pelo professor ao aluno. Os resultados revelaram diferenças significativas entre meninos e meninas do grupo de alunos com desempenho insatisfatório, pois a maioria (83,3%) era do sexo masculino. Por outro lado, não se verificaram diferenças estatisticamente significantes quando comparados meninos e meninas do grupo com desempenho escolar satisfatório, embora a média de desempenho escolar das meninas tenha sido maior. Em relação à percepção de seus professores, foram observadas diferenças nos dois grupos. Alunos com desempenho satisfatório se percebem mais elogiados e são escolhidos como ajudantes na sala de aula, enquanto alunos com desempenho insatisfatório acreditam receber mais críticas de seus professores e são vistos como mais indisciplinados. Os dados permitem discutir as relações vinculares entre alunos e professores, as influências das vivências e experiências no momento da aprendizagem e como essas influenciam o interesse e a motivação dos estudantes.
Academic achievement: comparative analysis by gender and student perception
Keywords: Relações interpessoais; Percepção de alunos; Desempenho escolar; Interpersonal Relations; Perception of students; Academic achievement